Peran Digital Leadership Dan Literasi Digital Terhadap Kinerja SDM: Adopsi Teknologi Digital Sebagai Variabel Moderasi Pada UMKM Kab. Bekasi - Irma Rohmatul Manan; Ahmad Gunawan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to have human resources (HR) who are adaptive, competent, and able to utilize digital technology optimally. In this context, the role of digital leadership and digital literacy is an important factor in improving human resource performance. This study aims to analyze the influence of digital leadership and digital literacy on human resource performance with the adoption of digital technology as a moderation variable in MSMEs in Bekasi Regency. The research method used is a quantitative approach with survey techniques through the distribution of questionnaires to MSME actors who have applied digital technology in their business activities. The data was analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results of the study show that digital leadership and digital literacy have a positive and significant effect on human resource performance. In addition, the adoption of digital technology has been proven to strengthen the relationship between digital leadership and HR performance, as well as between digital literacy and HR performance. These findings indicate that the success of improving the performance of MSME human resources is not only determined by the quality of leadership and digital literacy, but also by the level of adoption of digital technology that is carried out effectively. This research is expected to make a theoretical contribution to the development of digital-based human resources studies and become a practical reference for MSME actors and policy makers in designing strategies to strengthen human resources in the digital economy era.